STATUS HUKUM KEPEMILIKAN TANAH YAYASAN YANG BERSERTIPIKAT ATAS NAMA PERSEORANGAN - Wenni Indita Yuliardani (universitas islam darul ulum lamongan, 2017)
This legal research is conducted because in reality still found the right to land owned by the foundation on behalf of the management. This fact raises legal issues concerning the legal status of ownership of certified foundations in the name of individuals. The focus of this legal research is to find a systematic explanation of the validity of the status of land owned by the foundation certified on behalf of the individuals based on the Foundation Law and the legal efforts of the foundation's board so that the foundation's land is certified on behalf of the Foundation. The problem approach used is the statute approach, the conceptual approach, and the historical approach. Based on the legal research conducted, it can be concluded that (1) the legislation, the foundation is one of the legal entity that can own the right to land so that the foundation land still certified on behalf of the individual is legitimate as the property of the foundation, by certain legal effort; (2) the legal remedies that a foundation can make for the land owned by a foundation certified in the name of an individual may be turned on behalf of the foundation by a reversal of the name on the basis of proof of release of the landrights by the person in the certificate as the owner of the foundation's land or heirs if the person concerned has passed away, or the board of the foundation filed a lawsuit to ensure that the land of the foundation certified on behalf of an individual is designated as the property of the foundation.